2021
DOI: 10.1021/acschemneuro.1c00017
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Depletion of Sphingolipids Reduces Cell Surface Population of the Human Serotonin1A Receptor due to Impaired Trafficking

Abstract: Sphingolipids and their metabolites are increasingly implicated in the pathogenesis of many metabolic and neurological diseases. It has been postulated that sphingolipids coalesce with cholesterol to form laterally segregated lipid domains that are involved in protein sorting and trafficking. In this work, we have explored the effect of metabolic depletion of sphingolipids on cell surface expression of the human serotonin 1A receptor, a neurotransmitter G protein-coupled receptor. We used fumonisin B 1 (FB 1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Use of a mycotoxin known to reduce sphingolipid content reduces the amount of cell surface localised 5HT-1A receptor [111], in line with earlier results indicating the same treatment reduced specific ligand binding and associated downstream cAMP signalling for this receptor [48]. In contrast, similar studies on the angiotensin II type 1A receptor and the bitter taste receptor, T2R14, indicated no change in receptor signalling as a result of sphingomyelin depletion [112].…”
Section: Gpcrs and Sphingolipids And Glycolipidssupporting
confidence: 79%
“…Use of a mycotoxin known to reduce sphingolipid content reduces the amount of cell surface localised 5HT-1A receptor [111], in line with earlier results indicating the same treatment reduced specific ligand binding and associated downstream cAMP signalling for this receptor [48]. In contrast, similar studies on the angiotensin II type 1A receptor and the bitter taste receptor, T2R14, indicated no change in receptor signalling as a result of sphingomyelin depletion [112].…”
Section: Gpcrs and Sphingolipids And Glycolipidssupporting
confidence: 79%
“…We previously showed that the N‐terminal myc‐tagged serotonin 1A receptors expressed in HEK‐293 cells retain all characteristics of the native serotonin 1A receptor in terms of ligand binding, G‐protein coupling and cellular signaling 43,61 . To monitor endocytosis of the serotonin 1A receptor in HEK‐5‐HT 1A R cells, we used a quantitative flow cytometric assay, previously developed by us 43–46,54 . This assay allows quantitative measurement of receptor endocytosis by quantifying the cell surface population of serotoinin 1A receptors from a large number of cells using an anti‐myc antibody conjugated to Alexa Fluor 488 against the N‐terminal myc‐tag of the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…These results highlight the complexity involved in these two processes and emphasize the relevance of the actual methodology used to deplete cholesterol (for more details, see Sarkar et al, 2017 ; Kumar and Chattopadhyay, 2021a ). In addition, we showed that inhibition of sphingolipid biosynthesis could affect trafficking of the serotonin 1A receptor ( Kumar et al, 2021 ).…”
Section: Endocytosis and Cellular Trafficking: New Paradigm In Slos R...mentioning
confidence: 99%